2018
DOI: 10.1186/s12882-018-0944-z
|View full text |Cite
|
Sign up to set email alerts
|

Gene alterations in monocytes are pathogenic factors for immunoglobulin a nephropathy by bioinformatics analysis of microarray data

Abstract: BackgroundImmunoglobulin A nephropathy (IgAN) is the most frequent primary glomerulopathy worldwide. The study aimed to provide potential molecular biomarkers for IgAN management.MethodsThe public gene expression profiling GSE58539 was utilized, which contained 17 monocytes samples (8 monocytes samples isolated from IgAN patients and 9 monocytes samples isolated from healthy blood donors). Firstly, differentially expressed genes (DEGs) between the two kinds of samples were identified by limma package. Afterwar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…HDAC10 is also a latent biomarker in immunoglobulin A nephropathy (IgAN) and renal fibrosis as well [ 111 , 112 ]. HDAC10 protein levels are significantly higher in fibrotic kidneys.…”
Section: Hdac10 In Other Non-tumor Diseases and Its Pathophysiological Functionsmentioning
confidence: 99%
See 1 more Smart Citation
“…HDAC10 is also a latent biomarker in immunoglobulin A nephropathy (IgAN) and renal fibrosis as well [ 111 , 112 ]. HDAC10 protein levels are significantly higher in fibrotic kidneys.…”
Section: Hdac10 In Other Non-tumor Diseases and Its Pathophysiological Functionsmentioning
confidence: 99%
“…However, piceatannol treatment does not diminish HDAC10 expression but the results hint that HDAC10 may regulate renal fibrosis via other signaling pathways [ 111 ]. To determine a biomarker for IgAN, Guo et al [ 112 ] utilized samples from the Gene Expression Omnibus (GEO) database and found that HDAC10 existed in monocytes of IgAN samples, which enriches in both alcoholism and chromatin modifying enzymes via construction of functional interaction (FI) network.…”
Section: Hdac10 In Other Non-tumor Diseases and Its Pathophysiological Functionsmentioning
confidence: 99%
“…Previous two studies have suggested that the decrease in number and function of NK cells were associated with the disease progression of IgAN [ 31 , 32 ]. Altered monocyte gene expression patterns and numbers were found to be pathogenic factors in IgAN [ 33 , 34 ]. Higher respiratory burst and metabolic reprogramming in monocytes have been linked to the pathogenesis of IgAN [ 30 , 35 ].…”
Section: Resultsmentioning
confidence: 99%
“…In particular, the elevated expression of NDUFS3 and TNFRSF1A suggested the altered mitochondrial respiratory function and death receptor homeostasis in monocytes. Intriguingly, two recent studies have confirmed that TNF gene expression levels in monocytes from IgAN patients are reduced compared with those from healthy donors [ 30 , 34 ], further suggesting a reduced TNF alpha signaling pathway in IgAN patients. In our scRNA-seq results, we find a classical monocyte subset is slightly increased in IgAN.…”
Section: Discussionmentioning
confidence: 98%